Penerapan Pembelajaran Diferensiasi Untuk Meningkatkan Hasil Belajar PAI Pada Konteks Menanamkan Nilai Saling Menghargai Dalam Keragaman Peserta Didik Kelas IV SDIP As-Syafiiyah Tanggulangin - Istiqomah, Farihatul; Nasir, Moch.; Marzuki, Ahmad (Impressive: Journal of Education, 2023)
This research was conducted with the aim of being able to find out the learning outcomes of students after applying differentiation learning. The type of research used is Classroom Action Research (PTK) which lasts for two cycles through four stages (1) planning (2) implementation (3) observation (4) reflection. The research data consisted of teacher activity data, student activity data, student learning outcomes data. Data collection techniques used in this study are observation and tests. The research subjects were all fourth grade students at SDIP As-Syafiiyah Tanggulangin with a total of 34 students. The classical mastery criteria in this study were is greater than or equal to 80% of students obtaining learning outcomes in accordance with the specified KKM, namely 78. The results of this study indicate that by applying differentiation learning in PAI learning students can respect each others surroundings, and student learning outcomes are increasing. This is indicated by the increase in teacher activity in cycle I reaching 83.92, and in cycle II reaching 96.42. As for the activities of students in the first cycle, it was 51.78, and in the second cycle it was 94.64. The learning outcomes of students in cycle I reached an average of 68.85 with a classical mastery percentage of 38.23%, while in cycle II it achieved an average of 80.58 with a classical mastery of 82.36%. Based on the results of the research that has been done, it can be concluded that differentiation learning in PAI subjects in the context of mutual respect in diversity can improve the learning outcomes of fourth grade students at SDIP As-Syafiiyah Tanggulangin